1990
DOI: 10.1109/10.52332
|View full text |Cite
|
Sign up to set email alerts
|

Frequency analysis of the peripheral pulse wave detected in the finger with a photoplethysmograph

Abstract: A photoelectric plethysmograph is described that performs a frequency analysis of the peripheral volume pulse wave using a portable computer. It was used to determine how the pulse shape varied with age using 54 subjects in three age groups, 10-29, 30-59, and 60-89 years. The youngest group had a larger power in the second harmonic, (normalized to the fundamental), with p less than 0.05 than the older two groups. The decrease of power in the harmonics of the peripheral pulse wave with age may be a useful nonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 7 publications
2
51
0
Order By: Relevance
“…The PPG AC amplitude normalization was done to ease visualization and comparison. A pulse shape with the similar PPG AC amplitude and heart rate is selected for the subjects in each age group to minimise the variability in rising edge due to PPG AC amplitude normalization (Sherebrin and Sherebrin 1990). Examples of PPG signals of index finger of right arm of healthy young and aged female subjects are shown in Fig.…”
Section: Signal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The PPG AC amplitude normalization was done to ease visualization and comparison. A pulse shape with the similar PPG AC amplitude and heart rate is selected for the subjects in each age group to minimise the variability in rising edge due to PPG AC amplitude normalization (Sherebrin and Sherebrin 1990). Examples of PPG signals of index finger of right arm of healthy young and aged female subjects are shown in Fig.…”
Section: Signal Analysismentioning
confidence: 99%
“…Age related changes in shape characteristics in individual fingers (Sherebrin and Sherebrin 1990) and toe (Oliva and Roztocil 1996) have been investigated by frequency spectrum analysis, showing that there is a general reduction in the harmonic components of the pulse in older subjects (Shirouzu et al 1998). Analysis of PPG pulse contour in the finger demonstrated that the time between the peaks of forward and reflected waves decreased in older subjects (Millasseau et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There has been published data in the literature, which quantify pulse transit timing changes with age [3,6]. Frequency analysis of the PPG signals at different body sites with respect to age has been carried out [7,8] and it has been shown that there is a general reduction in the harmonic components of the pulse in older subjects. Work has also been done using the second derivative of the photoplethysmogram (SDPPG) to study age-related indices and other risk factors for atherosclerotic vascular disease [9,10].…”
mentioning
confidence: 99%
“…However valuable information about cardiovascular vital parameters can be extracted from frequency-domain and time-frequency features of PPG [55][56][57][58]. FMD-induced changes in these features may help in a better evaluation of the endothelial function.…”
Section: Future Directionsmentioning
confidence: 99%